2013
DOI: 10.1080/15374416.2013.777916
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Maltreatment, Peer Victimization, and Depressive versus Anxiety Symptoms During Adolescence: Hopelessness as a Mediator

Abstract: Objective Extensive comorbidity between depression and anxiety has driven research to identify unique and shared risk factors. This study prospectively examined the specificity of three interpersonal stressors (emotional abuse, emotional neglect, and relationally-oriented peer victimization) as predictors of depressive versus anxiety symptoms in a racially-diverse community sample of adolescents. We expanded on past research by examining hopelessness as a mediator of the relationships between these interperson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 93 publications
2
63
1
2
Order By: Relevance
“…Thus, we will investigate whether early childhood and early adolescent maltreatment predict depression and anxiety symptoms more than mid-childhood maltreatment. Numerous studies demonstrated that child maltreatment is predictive of depression and anxiety symptoms (e.g., Collishaw et al, 2007;Hamilton et al, 2013;McGloin & Widom, 2001;Scott et al, 2010;Spinhoven et al, 2010) and impairments in cognitive functioning measured later in life (e.g., Gould et al, 2012;Hart & Rubia, 2012;Jaffee & Maikovich-Fong, 2011;Mills et al, 2011;Navalta, Polcari, Webster, Boghossian, & Teicher, 2006;Spann et al, 2012). There is also evidence from longitudinal studies that higher IQ was predictive of fewer symptoms of depression and anxiety (Kitano & Lewis, 2005;Koenen et al, 2009;Weeks et al, 2014).…”
Section: Empirical Model Of Resilience Process: the Role Of Timing Ofmentioning
confidence: 94%
“…Thus, we will investigate whether early childhood and early adolescent maltreatment predict depression and anxiety symptoms more than mid-childhood maltreatment. Numerous studies demonstrated that child maltreatment is predictive of depression and anxiety symptoms (e.g., Collishaw et al, 2007;Hamilton et al, 2013;McGloin & Widom, 2001;Scott et al, 2010;Spinhoven et al, 2010) and impairments in cognitive functioning measured later in life (e.g., Gould et al, 2012;Hart & Rubia, 2012;Jaffee & Maikovich-Fong, 2011;Mills et al, 2011;Navalta, Polcari, Webster, Boghossian, & Teicher, 2006;Spann et al, 2012). There is also evidence from longitudinal studies that higher IQ was predictive of fewer symptoms of depression and anxiety (Kitano & Lewis, 2005;Koenen et al, 2009;Weeks et al, 2014).…”
Section: Empirical Model Of Resilience Process: the Role Of Timing Ofmentioning
confidence: 94%
“…In a broad sense, emotion-related constructs, self-perceptions, and emotional and behavioral reactions to peer victimization were studied as potential explanations for internalizing problems in victimized adolescents. For instance, hopelessness was examined in two studies, one of which did not find a link between relationally oriented peer victimization and the mediator (Hamilton et al 2013), thus did not test for mediation, whereas the second study (based on the same sample) showed that hopelessness mediated the link between peer victimization and depression but only among adolescents with low future orientation . Other emotion-related mediators included rejection sensitivity, which describes anxious expectations of not being accepted or of being overtly rejected.…”
Section: Mediators On Associations Between Peer Victimization and Intmentioning
confidence: 99%
“…Néanmoins, on associe à la maltraitance psychologique des symptômes dépressifs et d'anxiété chez les adolescents (Hamilton et al, 2013). Lorsque la maltraitance psychologique ou la négligence sont plus sévères durant l'enfance, on observe davantage d'agressivité chez les enfants d'âge scolaire, et ce, peu importe les abus concomitants (Manly, Kim, Rogosch et Cicchetti, 2001).…”
Section: Les Effets De La Maltraitance Psychologiqueunclassified
“…Plusieurs études, une recension et une récente méta-analyse identifient plus spécifiquement les difficultés des enfants qui se considèrent rejetés par leurs parents : instabilité émotionnelle, difficultés associées au manque d'estime d'euxmêmes, perception négative du monde, hostilité et agressivité qui donnent lieu à des troubles de la conduite, à des comportements externalisés, voire délinquants (Akse, Hale, Engels, Raaijmakers et Meeus, 2004;Chang, Schwartz, Dodge et McBride-Chang, 2003;Khaleque et Rohner, 2012;Rohner et al, 2005a). Ainsi, un nombre croissant d'études sur les effets de la maltraitance psychologique ou de la négligence affective des enfants les associent à des facteurs de risque non spécifiques pour un ensemble de problèmes de comportement et de troubles affectifs (Aust, Hartwig, Heuser et Bajbouj, 2013;Hamilton et al, 2013;Manly et al, 2001). Une étude longitudinale effectuée auprès de 388 adolescents a par ailleurs démontré que l'hostilité parentale telle que mesurée lorsqu'ils étaient en 7 e , 8 e et 9 e année les prédisposait à des problèmes de comportements en 10 e année (Ge et al, 1996), ce qui renforce l'éventualité d'une relation de causalité.…”
Section: Les Effets De La Maltraitance Psychologiqueunclassified